Adoption of woreda participatory land use planning (WPLUP) in pastoral areas by government of Ethiopia - CGIAR Research Program on Livestock (2019)
Woreda (district) participatory land use planning (WPLUP) is a government process developed with technical assistance of ILRI. WPLUP provides for the involvement of local communities in the land use planning and development planning process, giving greater opportunities for their priorities to be considered. WPLUP can protect pastoral land uses and give greater security of rights of access to pastoralists and other users.